2007
DOI: 10.1111/j.1479-828x.2007.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth restriction and other factors associated with neonatal death in New Zealand

Abstract: This study emphasises the importance of suboptimal fetal growth as an important risk factor for neonatal death especially when customised centiles are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Recent studies in France and New Zealand found that 17% and 13% of all neonatal deaths were below the tenth percentiles of national standards [27], [28]. This compared to studies of stillbirth where between 40% and 60% are associated with growth restriction [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in France and New Zealand found that 17% and 13% of all neonatal deaths were below the tenth percentiles of national standards [27], [28]. This compared to studies of stillbirth where between 40% and 60% are associated with growth restriction [29].…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible explanations for especially large differences in growth between survivors and non‐survivors in the youngest individuals. On one hand, this could be due to factors impacting health and growth in the gestational periods, as maternal factors are known to be a major driver of mortality in the first month of life (Abdullah et al, 2016 ; Battin et al, 2007 ; Bourgeois, 1951 ). However, in part because the study design excluded deaths due to severe prematurity or gestational deaths, those where cause of death was unknown, and sudden deaths in infancy, sample size is small in this age group, particularly in the accidental death group.…”
Section: Discussionmentioning
confidence: 99%
“…IUGR is more difficult to define and measure but approximately 10% of all infants will be born small for gestational (SGA) defined as birthweight < 10 th customised birthweight centile and at least two thirds of these have evidence of abnormal uterine and umbilical Doppler waveforms if diagnosed prior to birth suggesting significant utero-placental disease and fetal growth restriction [2]. Infants who are born growth restricted with or without maternal preeclampsia are at increased risk of morbidity and mortality during the perinatal period [35], and this risk continues into childhood and adult life with higher rates of neurosensory disability, cognitive impairment, short stature, hypertension, diabetes and long term cardiovascular disease [611]. Women with preeclampsia and/or IUGR fetuses are more likely to require preterm delivery, with over one third of women with preeclampsia and 15% of SGA infants delivering <37 weeks [12].…”
Section: Introductionmentioning
confidence: 99%
“…Women with preeclampsia and/or IUGR fetuses are more likely to require preterm delivery, with over one third of women with preeclampsia and 15% of SGA infants delivering <37 weeks [12]. Iatrogenic preterm birth often results in operative delivery and therefore has inherent risks to the mother and results in the significant additional risks of prematurity for an already compromised infant [3, 1315]. …”
Section: Introductionmentioning
confidence: 99%